Sistem Pakar Diagnosis Penyakit Tanaman Kopi Menggunakan Metode Certainty Factor - Harben Harben Fikri Basya; Galang Ramadhan (Universitas Mercu Buana Yogyakarta, 2024)
Abstract. The lack of agricultural experts in providing information about plant diseases to cultivators can have an impact on coffee plant cultivators where farmers play a role in providing direction, guidance, and counseling about coffee plant problems faced by farmers. The development of information technology today has a significant impact in various fields including agriculture/plantation. Therefore, technological developments are also utilized by coffee plant cultivators to obtain information as early as possible about the types of diseases suffered by cultivated plants and how to deal with them. The purpose of this study was to design an expert system in diagnosing coffee plant diseases using the Certainty Factor method. Certainty Factor is used because this method can help to overcome uncertainty in decision making and provide a percentage of diagnostic results. Certainty Factor can occur under various conditions, which for this study have several conditions or symptoms of disease that determine whether a coffee plant is attacked by disease or not. From the results of testing the program system, obtained the same results with manual calculations using the Certainty Factor method. So it can be said that this system can diagnose coffee plant diseases and provide solutions. Keywords: Expert System, Plant diseases, Certainty Factor